Urgensi Kehadiran Bank Tanah Sebagai Alternatif Memulihkan Perekonomian di Indonesia - Fidri Fadillah Puspita; Fitri Nur Latifah; Diah Krisnaningsih (Jurnal Ilmiah Ekonomi Islam, 2021)
The formation of the land bank has been successfully built since the declaration of Government rule number 64 2021 about the structure of the land bank. According to the rule, the structure of the land bank has several objectives to distribute the owned land to achieve the sustainability of the economy. However, we focus on the urgency of existence from the land bank towards economic sustainability. By showing the creation of a land bank that is related to land acquisition, especially for the development of the infrastructure, therefore the prices tend to be expensive. The purpose of the current research is to understand how is the concept of a land bank to organize land assets that would be utilized and distributed. The current research is designed by qualitative and using the yuridis normative. Therefore, the urgency of the land bank can overcome the bad possibilities such as claimant, confrontation, and liberalization. At last, enhancing the land bank maximally requires some priority and evaluation during the process.